Soybean cyst nematode (Heterodera glycines) resistant cultivar rotation system impacts nematode population density, virulence, and yield. (March 2022) - Thapa, Sita; Cole, Emilie; Howland, Amanda D.; Levene, Brian; Quintanilla, Marisol
Abstract: Soybean cyst nematode (SCN) is the most economically important pathogen of soybeans in the United States. The most effective SCN management practice is the use of resistant cultivars; however, continuous use of cultivars derived from a single line of resistance results in selection for SCN virulent populations. A four-year field study (2017–2020) was conducted in Michigan to evaluate the impact of six soybean rotation systems with cultivars derived from PI548402 (5DV) and PI88788 (8DV) on SCN population development, virulence, and soybean yield. The rotation systems were: 1) 8DV/5DV/8DV/5DV, 2) 5DV/5DV/5DV/5DV, 3) 8DV/Susceptible (SDV)/5DV/8DV, 4) 5DV/SDV/8DV/5DV, 5) 8DV/8DV/8DV/8DV, and 6) 5DV/SDV/SDV/SDV. SCN population levels were significantly lower in the 5DV/8DV rotation in 2018 compared to the 5DV/SDV rotation. In 2020, SCN population levels were the lowest in the rotation system 8DV/5DV/8DV/5DV and the highest in the continuous 5DV soybeans. In 2017, there were no substantial soybean yield differences among the differing systems, but for the remainder of the trial, the 5DV/8DV rotations had the highest yields. HG type tests showed that rotation of resistance sources can alter the virulence of the SCN population. The initial 2017 SCN population was HG type 1.2. The final populations in 2020 for the rotation systems 8DV/5DV/8DV/5DV, 5DV/5DV/5DV/5DV, and 8DV/SDV/5DV/8DV was HG type 1.2.5.7, and HG type 1.2.3.5.6.7 for the other rotation systems 5DV/SDV/8DV/5DV, 8DV/8DV/8DV/8DV, and 5DV/SDV/SDV/SDV. Based on the results of the field trial, a greenhouse trial was conducted where we found that a Michigan SCN population from continuous PI88788 sources of resistance can also reproduce on Peking. These findings indicate rotating PI548402- and PI88788-derived cultivars can reduce SCN density and maintain high soybean yields; thus rotating these two sources of resistance with non-host rotations might delay the aggressiveness of SCN populations further, reducing soybean yield loss. Highlights: Rotation. PI548402 and PI88788. Reduce SCN population densities. Increase soybean yields.